2022
DOI: 10.2176/nmc.tn.2021-0179
|View full text |Cite
|
Sign up to set email alerts
|

3D Turbo Spin-echo MRI-based Mechanical Thrombectomy at Middle Cerebral Artery Bifurcations

Abstract: We describe three cases with acute middle cerebral artery (MCA) occlusion. From the preoperative MRI, including three-dimensional turbo spin-echo sequences using T1WI and T2WI, we assessed both thrombus configuration and arterial anatomy at the MCA bifurcations. For efficient endovascular thrombectomy, we identified the applied MCA segment 2 (M2) branch, in which the main thrombus was buried. Sufficient recanalization after a single pass was achieved and the patients made a marked recovery. Although mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…However, if preoperative MRI evaluation is done, 3D turbo spin-echo sequences may reveal the anatomy of the occluded vessel. 13 ) Moreover, as in Case 1, because the fenestration may be exposed during treatment, performing treatment with a sufficient understanding of the anatomy can reduce the risk of complications. Therefore, although the time to reperfusion is important, the anatomy must still be evaluated to avoid complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, if preoperative MRI evaluation is done, 3D turbo spin-echo sequences may reveal the anatomy of the occluded vessel. 13 ) Moreover, as in Case 1, because the fenestration may be exposed during treatment, performing treatment with a sufficient understanding of the anatomy can reduce the risk of complications. Therefore, although the time to reperfusion is important, the anatomy must still be evaluated to avoid complications.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, several different methods of visualization have been reported. Ohara et al 10) created T1- and T2-weighted images using a 3D-turbo spin-echo sequence to identify the thrombus and arterial anatomy. It has been reported that in cases involving branches of the middle cerebral artery, multiplanar reconstruction has been used to assess the location and size of thrombi and intramural hematomas; additionally, the effectiveness of the 3D-turbo spin-echo sequence has been advocated.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 patients with acute basilar artery occlusion during this period underwent the following MRI protocol. 11 ) Using 3.0 T MRI (Skyra system; Siemens, Erlangen, Germany), patients with acute ischemic stroke underwent diffusion-weighted imaging (DWI), 3D time-of-flight magnetic resonance angiography (MRA), T2*WI, fluid-attenuated inversion recovery, and 3D-TSE T1WI and T2WI. The total scan time of our stroke protocol was 9 min and 47 sec.…”
Section: Methodsmentioning
confidence: 99%
“…8) A few studies of mechanical thrombectomy have em-ployed magnetic resonance imaging (MRI) to detect occluded vessels in the anterior circulation, and we have demonstrated the efficacy of three-dimensional turbo spinecho (3D-TSE) sequences using T1WI and T2WI to evaluate both thrombus configuration and arterial anatomy at the middle cerebral artery bifurcations. [9][10][11] In this study, we applied 3D-TSE T2WI to examine the vascular structure of the posterior circulation, including a comparison of vessel diameters between the posterior communicating artery (PCoA) and the P1 segment of the posterior cerebral artery (PCA). Our findings indicate the utility of 3D-TSE T2WI for identifying the mechanism of posterior circulation cerebral ischemia and achieving a safe and efficient mechanical thrombectomy.…”
Section: Introductionmentioning
confidence: 99%